Roadmap of the key variables and action framework for attaining sdg 4-education 2030 agenda in Nigeria (2019)
In order to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all, which is the SDG 4-Education 2030 Agenda, various countries have been developing broad and specific action plans towards the attainment of the goal. There exists in Nigeria a broad action framework for all the SDGs, as contained in Nigeria's Road to SDGs. There is, however, no concrete specific action tasks and the timeline towards SDG 4-Education 2030 Agenda in Nigeria. This paper is therefore written to guide education policy planners and decisionmakers in Nigeria on the key variables and specific action framework/timeline for achieving the goal. The paper begins with the discussion of the SDG 4-Education 2030 targets. It also discusses the key features and policies priorities of SDG4 as well as the implications for educational development. It equally identifies and discusses the key variables that Nigeria must focus attention on as follows: policy and planning, financing, advocacy and communication, capacity development and technical assistance, coordination, and partnership, as well as monitoring. It also makes suggestions on the specific tasks and the timeline for the achievement of these variables. The paper concludes that the achievement of the SDG 4-Education 2030 vision in Nigeria must be seen by education policy planners and decision-makers as a serious issue of national importance. Therefore, the country needs to display aggressive pursuance of the goal not in terms of a broad framework, but in terms of specific action tasks